1993
DOI: 10.1002/jctb.280580102
|View full text |Cite
|
Sign up to set email alerts
|

Sodium inhibition and sulphate reduction in the anaerobic treatment of mussel processing wastewaters

Abstract: An anaerobic filter treating high saline wastewaters from a sea food processing industry was subjected to sodium and sulphate shocks. Sodium concentrations ranging from 5 to 12 g dm−3 had no significant influence on the methane production rate, with maximum value of 15 kg COD CH 4 m−3 day−1. The sulphate‐reducing capacity of the filter was estimated at 2.2 kg SO42‐ m−3 day−1. When using propionic or acetic acid as substrates, the sulphate‐reducing activities were 0.021 and 0.006 g SO42‐ g−1 VSS day−1 respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 10 publications
3
29
0
2
Order By: Relevance
“…This shows that the rate of biodegradation by the propionic utilizers was significantly decreased in the presence of NaCl. This finding is in agreement with Soto et al (1993) who found that an increase in the sodium concentration from 5 to 12 gNa + l -1 resulted in an increase in the propionate to acetate ratio from 0.7 to 1. However, Feijoo et al (1995) using granular non-adapted biomass found that nbutyrate utilisers were the most sensitive group of bacteria.…”
Section: Discussionsupporting
confidence: 94%
“…This shows that the rate of biodegradation by the propionic utilizers was significantly decreased in the presence of NaCl. This finding is in agreement with Soto et al (1993) who found that an increase in the sodium concentration from 5 to 12 gNa + l -1 resulted in an increase in the propionate to acetate ratio from 0.7 to 1. However, Feijoo et al (1995) using granular non-adapted biomass found that nbutyrate utilisers were the most sensitive group of bacteria.…”
Section: Discussionsupporting
confidence: 94%
“…As a result, the specific surface area is increased, the substrates are easily accessible to anaerobic microbes [83,106,107]. [83,109] 7 Lignocellulosic biomass Acid pretreatment is an expensive process due to high cost of acids and the additional cost for neutralizing the acidic conditions prior to the AD process [106,112,113] 8 Waste water Sodium is more toxic to propionic acid utilizing bacteria as compared to other VFA degrading bacteria [114] 9 Sludge…”
Section: Chemical Pretreatmentmentioning
confidence: 99%
“…Kim et al (2000) contemplated hindrance because of the sodium particle dose on the AD bioreactor running on thermophilic zone of FW and stated that sodium at a concentration of >5 g/L brought about decrease in biogas generation. Sodium is more lethal to propionic acid utilizing microorganisms when contrasted with other VFA debasing microorganisms in the AD system (Soto et al, 1993). The inhibitory effect of potassium begins at the level of 400 mg/L.…”
Section: Effect Of Additive and Trace Metals On Anaerobic Digestionmentioning
confidence: 97%